Evaluation of In Vitro Antioxidant Activity of the Water Extract Obtained from Dried Pine Needle (Pinus densiflora) - Kim, Joo-Shin (Prev Nutr Food Sci, 2018)
Antioxidant activities of water extracts obtained from dried pine needle (Pinus densiflora) were measured at 0, 4, 20, 100, 500, 1,000, and 1,200 ppm and compared with those of phenolic compounds of butylated hydroxyanisole, butylated hydroxytoluene, tert-butylhydroquinone, ferulic acid, and α-tocopherol. The activity was determined as the ability to scavenge 1,1-diphenyl-2-picrylhydrazyl radical and hydrogen peroxide, reductive power, and inhibition of lipid peroxidation in a linoleic acid system using the ferric thiocyanate method and thiobarbituric acid method, respectively. Pine needle water extract (PNWE) exhibited antioxidant activity in a concentration-dependent mode at the same parameters mentioned above, and a significant difference (P<0.05) was observed at 1,000 ppm. The protective activity of PNWE as a potent antioxidant in a non-cellular system was compared with that of phenolics at 150.67 μg/mL in the two assays using biological cellular systems, namely 2,2′-azobis(2-amidinopropane) dihydrochloride-initiated hemolysis and Fe(2+)-induced lipid peroxidation, using rat red blood cells and rat brain homogenate, respectively. The PNWE showed a strong power comparable to those of commercial phenolic compounds in biological systems. These results indicated that the protective activity of PNWE could be due to the presence of naturally-occurring phenolic compounds, which act as potent in vitro antioxidants in both non-cellular and cellular systems.